Understanding tobacco use and socioeconomic inequalities among men in Ghana, and Lesotho - Kwamena Sekyi Dickson; Bright Opoku Ahinkorah (BMC, 2017)
Abstract Background Tobacco use is one of the leading causes of preventable deaths and has become a significant public health issue. Previous studies have paid less attention to tobacco use and socio-economic equalities among men in developing countries. This study examines the relationship between tobacco use and socio-economic inequalities among men in Ghana and Lesotho. Methods The study made use of data from the 2014 Demographic and Health Survey (DHS) from Ghana, and Lesotho. Binary logistic regression was employed to examine the associations between socio-economic inequality characteristics of respondents and tobacco use. Results The results showed that the prevalence of tobacco use was high in Lesotho (47.9%) as compared to that of Ghana (6.3%). Tobacco use was generally high across all age groups in Lesotho and in contrast, it was relatively low across all ages in Ghana. A statistically significant association was found between all the socio-economic variables and tobacco use in both countries. The prevalence of tobacco use was smaller in age group 15-24 years compared to the age groups 25-34 years and 35-59 years in both Ghana and Lesotho, although the association is stronger in Ghana. The AOR's in Ghana are respectively 5.3 (95% CI: 3.29-8.59) and 9.7 (95% CI: 6.20-15.06), compared to respectively 1.7 (95% CI: 1.32-2.11) and 1.7 (95% CI: 1.36-2.12). Smoking prevalence was smaller in men with higher level of education compared to men with no education in both Ghana and Lesotho, although the association was weaker in Ghana. The AOR in Ghana is 0.1 (95% CI: (0.02-0.11), compared to 0.2 (95% Cl: (0.17-0.30). The prevalence of tobacco use was smaller among men in urban areas compared to rural areas in both Ghana and Lesotho, although the association is stronger in Ghana. The AOR in Ghana is 2.1 (95% CI: 1.67-2.73), compared to 1.6 (95% CI: (1.31-1.95). In both countries, prevalence of tobacco use was higher in men who are traditionalist/spiritualists or who had no religion compared to Christians, although the association was stronger in Ghana. The AOR in Ghana is 6.2 (95% CI: (4.42-4.09) compared to 1.7 (95% CI: (1.21-2.47). The prevalence of tobacco use was low among men with richest wealth status compared to men with poorest wealth status in both Ghana and Lesotho, although the association is weaker in Ghana. The AOR in Ghana is 0.1 (95% Cl: (0.06-0.17) compared to 0.4 (95% CI: (0.51-1.12). In relation to occupation, prevalence of tobacco use was smaller among professional workers compared to men in the Agricultural sector in both Ghana and Lesotho, although the association is stronger in Ghana. The AOR in Ghana is 9.3 (95% Cl: (4.54-18.99), compared to 3.5 (95% CI: (2.27-5.52). Formerly married men in both countries were more likely to use tobacco compared to currently not married men, although the prevalence was higher in Ghana. The AOR in Ghana is 1.6 (95% CI: (0.99-2.28)], compared to 1.4 (95% CI: (0.89-2.28) in Lesotho. Conclusion Although similar socio-economic inequality factors provided an understanding of tobacco use among men in Ghana and Lesotho, there were variations in relation to how each factor influences tobacco use.